Research on Detection of Sterol Doping in Sports by Electrochemical Sensors: A Review - Yunyan Sun (Journal of Analytical Methods in Chemistry)
The use of doping by athletes to improve performance is prohibited. Therefore, doping testing is an important step to ensure fairness in sports. Doping is gradually metabolized in the body and is therefore difficult to detect immediately by a common method. At the same time, the emergence of new doping agents poses a challenge for highly sensitive detection. Electrochemical sensors are a fast, highly sensitive, and inexpensive analytical detection technology. It provides qualitative and quantitative determination of analytes by altering the electrochemical signal of the analyte or probe at the electrode. In this min-review, we summarized the different electrochemical sensing strategies for sterol doping detection. Some of the representative papers were interpreted in detail. In addition, we compare different sensing strategies.